Modes of action of allelochemical alkaloids: interaction with neuroreceptors, DNA, and other molecular targets - Wink, Michael; Schmeller, Thorsten; Latz-Brüning, Birgit (Journal of chemical ecology, 1998)
Several alkaloids are toxic to insects and vertebrates and, in addition, can inhibit the growth of bacteria and plant seedlings. In vitro assays were established to elucidate their modes of action and to understand their allelochemical properties. Basic molecular targets studied, present in all cells, included DNA intercalation, protein biosynthesis, and membrane stability. The degree of DNA intercalation was positively correlated with inhibition of DNA polymerase I, reverse transcriptase, and translation at the molecular level and with toxicity against insects and vertebrates at an organismic level. Inhibition of protein biosynthesis was positively correlated with animal toxicity. Molecular targets studied, present only in animals, included neuroreceptors (alpha1, alpha2, serotonin, muscarinic, and nicotinic acetylcholine receptors) and enzymes related to acetylcholine (acetylcholine esterase and choline acetyltransferase). The degree of binding of alkaloids to adrenergic, serotonin, and muscarinic acetylcholine receptors was positively correlated in G-protein-coupled receptors. Receptor binding and toxicity was correlated in insects. The biochemical properties of alkaloids are discussed. It is postulated that their structures were shaped in a process termed “evolutionary molecular modeling” to interact with a single and, more often, with several molecular targets at the same time. Many alkaloids are compounds with a broad activity spectrum that apparently have evolved as “multipurpose” defense compounds. The evolution of allelochemicals affecting more than one target could be a strategy to counteract adaptations by specialists and to help fight off different groups of enemies.
Gesehen am 01.08.2023